Alveolar Soft Part Sarcoma Metastasizing to the Brain: A Rare Entity Revisited with Review of Recent Literature - Kaushal-Deep, Singh Mathuria (J Pediatr Neurosci, 2019)
A 20-year-old male patient presented with a recent history of two episodes of seizures and Glasgow Coma Scale of E3V3M6. He was drowsy at presentation with bradycardia. On further examination, he was found to be having a 10 × 6cm well-circumscribed mass in the right medial thigh whose fine needle aspiration cytology was suggestive of soft tissue sarcoma. Contrast-enhanced magnetic resonance imaging brain showed enhancing lobulated lesions in bilateral hemispheres with significant edema. A decision to decompress the intracranial space occupying lesion was taken. Left-sided larger brain lesions underwent total gross excision followed by excision of the thigh mass. Histopathology of brain lesion was suggestive of metastatic deposits of alveolar soft part sarcoma, whereas the thigh mass was suggestive of alveolar soft part sarcoma grade 2 according to Fédération Nationale des Centres de Lutte Contre Le Cancer grading system. Postoperative course of the patient was unremarkable and his general condition improved remarkably (Functional Assessment of Cancer Therapy–Brain version 4 score improvement >50% at 1 month). He is in follow-up for the last 12 months and currently has completed chemoradiotherapy and is living a self-sufficient life. Though patients with aforementioned rare diagnosis have overall poor prognosis, decompressive craniotomy with metastasectomy may improve the overall quality of life of such young patients, and further chemoradiotherapy may help in prolonging life with acceptable level of comorbidity. This case is being discussed here in terms of the rarity of the final diagnosis, the management strategy used, and the quality of life improvement.